Epithelioid Hemangioma of the Thoracic Spine: A Case Report and Review of the Literature. (2nd November 2019) - Okada, Eijiro; Matsumoto, Morio; Nishida, Mitsuhiro; Iga, Takahito; Morishita, Midori; Tezuka, Masaki; Mukai, Kiyoshi; Kobayashi, Eisuke; Watanabe, Kota
Abstract : Context: Osseous epithelioid hemangioma is uncommon, and reports of epithelioid hemangiomas of the spine are especially rare. Study Design: Case report. Findings: A 43-year-old male was referred to our department with progressive gait disturbance. CT scans showed a lucent mass in the vertebral body at the T3 level. MRI of the thoracic spine showed a strongly enhanced mass compressing the spinal cord. The patient underwent laminectomy from T2 to T4, debulking of the tumor, and posterior fusion from T1 to T5. After the operation, the patient's neurological status improved significantly, and he was able walk without assistance. Histological examination determined that the tumor was an epithelioid hemangioma. The patient was treated with 40 Gy radiation for local control of the tumor. The patient could walk without difficulty 12 months after the surgery. Conclusion: This is a rare example of an epithelioid hemangioma that developed in the thoracic spine and compressed the spinal cord, and was treated successfully.